2013
DOI: 10.1182/blood-2012-11-469122
|View full text |Cite
|
Sign up to set email alerts
|

Differential control of Helios+/− Treg development by monocyte subsets through disparate inflammatory cytokines

Abstract: Key Points Control of Helios+/− Treg subset development is mediated through distinct cytokines and monocyte subpopulations. CD16+ monocytes inhibit Helios+ Treg proliferation through IL-12, whereas CD16− monocytes suppress Helios− Treg development through TNF-α.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 46 publications
(48 reference statements)
2
33
1
Order By: Relevance
“…Considering the dual role of Tregs in EH, therapeutic interventions on the expanded Tregs seem complicated and warrant additional studies. With regard to how pMOs affect the Treg compartment, a few recent studies (24,34) revealed their inhibitory effect on Treg expansion, contrary to our current data. In the current study, we demonstrated that pMOs detected in the acute stage of EH were characterized by the potent ability to expand Tregs, probably through their increased production of IL-10 and their decreased production of IL-1b, TNF-a, and IL-6, which were quite different from those detected in healthy controls, ADEH 2 patients, and ADEH patients at the resolution stage.…”
Section: Hsv-specific Cd4contrasting
confidence: 99%
“…Considering the dual role of Tregs in EH, therapeutic interventions on the expanded Tregs seem complicated and warrant additional studies. With regard to how pMOs affect the Treg compartment, a few recent studies (24,34) revealed their inhibitory effect on Treg expansion, contrary to our current data. In the current study, we demonstrated that pMOs detected in the acute stage of EH were characterized by the potent ability to expand Tregs, probably through their increased production of IL-10 and their decreased production of IL-1b, TNF-a, and IL-6, which were quite different from those detected in healthy controls, ADEH 2 patients, and ADEH patients at the resolution stage.…”
Section: Hsv-specific Cd4contrasting
confidence: 99%
“…Both LPS and HMGB1 “mature” DC into potent immunostimulatory cells that provide the ample MHC, costimulatory molecules, and IL-1β, −6, −23, and IL-12p70 needed for Th1 and Th17 polarization 52 . Likewise, it has been recently established that IL-12p70 potently inhibits Treg proliferation 53 . Thus, IL-33 is an unconventional alarmin that fails to induce classical DC maturation or support Th1 immunity.…”
Section: Discussionmentioning
confidence: 99%
“…(19) Alternatively, purified CD14 + CD16 − cells and autologous CFSE-labeled CD4+ T cells (2:1 ratio) in the absence or presence of CD16+ monocytes (CD14+CD16 − to CD16+ monocyte ratio of 2:1) were cultured for 7 days with anti-CD3 antibody. In the T cell stimulation experiments that were performed in the absence of monocytes, purified, CFSE stained CD4+ T cells (1.25×10 5 cells/ml) were cultured for 7 days in plates pre-coated with anti-CD3 antibody (clone HIT3α, 1µg/ml).…”
Section: Methodsmentioning
confidence: 99%
“…(13,14) In turn, monocytes can trigger and polarize Th responses (15,16) as well as both stimulate and suppress T-cell responses, depending on monocyte subset and their activation state. (16,17) Indeed, we recently showed in non-SCD setting that CD16+ monocyte subset, which constitute only about 5–10% of total monocytes in healthy individuals, controls Treg/Th proliferation, (18) inhibiting specific Treg subsets (19) while promoting Th1 expansion via IL-12. (18) The role of HO-1 in polarization of T cell responses in human disease setting has not been investigated.…”
Section: Introductionmentioning
confidence: 99%